2004
DOI: 10.1159/000072024
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent High-Permeability Hemofiltration Modulates Inflammatory Response in Septic Patients with Multiorgan Failure

Abstract: Background/Aim: Continuous venovenous hemofiltration with high-permeability hemofilters is a novel approach in the adjuvant therapy of septic patients. High-permeability hemofilters are characterized by an increased pore size which facilitates the filtration of inflammatory mediators. The present study examines whether intermittent high-permeability hemofiltration has an immunomodulatory effect on polymorphonuclear leukocytes and mononuclear cells. Methods: Twenty-eight septic patients with acute renal failure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
1
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 13 publications
(18 reference statements)
0
19
1
3
Order By: Relevance
“…On the other hand, the same persistency of high levels of transmembrane clearance might be expected for other large solutes as cytokines, that is, the target solutes of this extracorporeal blood purification therapy. The slight difference between the 12-h albumin loss observed in our study and in the study by Morgera et al [26] could derive from the larger membrane used in our protocol (1.1 vs. 0.6 m 2 ) and from the higher albumin concentration observed in our experimental solution (the patient solution ) than the one observed in plasma of patients enrolled by Morgera et al [26] (3 vs. 2.5 g/dL).…”
Section: Discussioncontrasting
confidence: 84%
See 2 more Smart Citations
“…On the other hand, the same persistency of high levels of transmembrane clearance might be expected for other large solutes as cytokines, that is, the target solutes of this extracorporeal blood purification therapy. The slight difference between the 12-h albumin loss observed in our study and in the study by Morgera et al [26] could derive from the larger membrane used in our protocol (1.1 vs. 0.6 m 2 ) and from the higher albumin concentration observed in our experimental solution (the patient solution ) than the one observed in plasma of patients enrolled by Morgera et al [26] (3 vs. 2.5 g/dL).…”
Section: Discussioncontrasting
confidence: 84%
“…In a prospective randomized trial on 16 septic patients with AKI, Morgera et al [26] measured an albumin transmembrane loss of 1.14 g (Interquartile range [IQR] 0.65–1.92 g) in the first 30 min of a convective treatment performed with blood and replacement flows of 150 mL/min and 1,000 mL/h respectively. Although slightly higher, the albumin loss observed in our study is consistent with respect to the one obtained by Morgera et al [26]; in particular, an albumin transmembrane loss of 2.01–2.06 g (measured with lines and bags methods) was observed in first 30 min of the protocol (the single pass phase).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the end, 3 case reports [15,16,17], 3 studies on animals [18,19,20], 11 in-vitro/ex-vivo studies [13,21,22,23,24,25,26,27,28,29,30,] and 6 randomized clinical trials/observational studies [14,31,32,33,34,35] fulfilled optimum criteria. The main results deriving from this pool constitute this review.…”
Section: Introductionmentioning
confidence: 99%
“…We recently showed that high cutoff hemofiltration can be safely applied in critically ill patients (14). We also showed that polymorphonuclear leukocyte function and lymphocyte proliferation are positively influenced by this new procedure (19,20).…”
mentioning
confidence: 98%